THE EFFECT OF ORGANIZATIONAL INDUCEMENTS ON TURNOVER INTENTIONS: STUDY AT PT XYZ - Norma, Dejita; Nissa’ah, Maghfirotun (Airlangga Development Journal, 2024)
Turnover intention has become a serious factor that needs to be considered in organizational development. The solution to be able to generate Turnover Intention is to create commitment to employees for the organization by providing competitive incentives. This study aims to determine the effect of Organizational Inducements on Turnover Intention mediated by Affective Commitment. This study uses a quantitative approach using questionnaires and the Partial Least Square (PLS) method using SmartPLS3. Respondents in this study were permanent employees of PT XYZ around 100 people. The results is there is a significant and insignificant effect of Organizational Inducements on Turnover Intention. It shows the influence and significance of Affective Commitment as a mediation for PT XYZ employees. These results conclude that Affective Commitment can make full mediation of Material Inducements on Turnover Intention and full mediation of Development Inducements on Turnover Intention.